2003
DOI: 10.4049/jimmunol.170.9.4767
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation of I-κB Kinase α/β by Protein Kinase C-Dependent c-Src Activation Is Involved in TNF-α-Induced Cyclooxygenase-2 Expression

Abstract: The signaling pathway involved in TNF-α-induced cyclooxygenase-2 (COX-2) expression was further studied in human NCI-H292 epithelial cells. A protein kinase C (PKC) inhibitor (staurosporine), tyrosine kinase inhibitors (genistein and herbimycin A), or a Src kinase inhibitor (PP2) attenuated TNF-α- or 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced COX-2 promoter activity. TNF-α- or TPA-induced I-κB kinase (IKK) activation was also blocked by these inhibitors, which reversed I-κBα degradation. Activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
106
1
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(118 citation statements)
references
References 48 publications
9
106
1
2
Order By: Relevance
“…In these cells, JAK2 is involved in the activation of NF-jB; JAK2 may activate IKK via the downstream pathways PI3K/Akt [24,25] and/or PKC/c-src [26]. The IL-12-and IL-23-activated JAK2 are phosphorylated at multiple tyrosine residues, and these serve as docking sites for other signal-transducing proteins containing src homology 2 (SH2) domains [18].…”
Section: Expression Of Il-12 Il-23 and Il-27 Receptor Subunits In Hmentioning
confidence: 99%
“…In these cells, JAK2 is involved in the activation of NF-jB; JAK2 may activate IKK via the downstream pathways PI3K/Akt [24,25] and/or PKC/c-src [26]. The IL-12-and IL-23-activated JAK2 are phosphorylated at multiple tyrosine residues, and these serve as docking sites for other signal-transducing proteins containing src homology 2 (SH2) domains [18].…”
Section: Expression Of Il-12 Il-23 and Il-27 Receptor Subunits In Hmentioning
confidence: 99%
“…Proline-rich tyrosine kinase (Pyk2) 3 (18,19) and p53/Lyn p56 (20) have roles in TNF-induced neutrophil activation; Etk/Bmx in TNF-induced endothelial cell migration and angiogenesis; c-Src in TNF-induced NF-B activation in the marrow macrophages (21,22); and TNF in regulation of gap junctions in airway epithelial cells (23). Pyk2 has also been implicated in TNF-induced JNK activation (24).…”
Section: Tnf Activates Syk Proteinmentioning
confidence: 99%
“…Involvement of members of the src kinase family required for in vivo Bcr-Abl leukemogenic properties (Hu et al, 2004), and known to stimulate NIK activity and to phosphorylate IKK directly (Huang et al, 2003) has also been reported. The present and previous studies (Constantino Rosa Santos et al, 2001) agree that the TEL-Abl oncogene, as well as Bcr-Abl, activates NF-kB but in a manner that presumably involves IKKa and do not strongly affect the p65/RelA nuclear translocation process (Figure 2a).…”
Section: Discussionmentioning
confidence: 96%